Reconstructing the Paradigm of Destination Development Through the Concept of Regenerative Tourism: A Phenomenological Study on Ecotourism Practices in the Jatigede Reservoir - Pijar Dwi Istio Prameswara; Andari, Rini; Puspito Diyah Setiyorini, Heri (JURNAL MANAJEMEN MOTIVASI, 2026)
Tourism destination development remains dominated by sustainability approaches that focus on minimizing impacts rather than restoring socio-ecological systems. This study aims to reconstruct a destination development paradigm through regenerative tourism in the Jatigede Reservoir, Indonesia. Using a qualitative phenomenological approach, data were collected from 15 ecotourism actors through interviews, observation, and documentation, and analyzed using Moustakas’ framework. The findings reveal five dimensions of regenerative development: ecosystem restoration, local economic empowerment, cultural revitalization, multi-stakeholder collaboration, and community adaptation. These findings provide a locally grounded regenerative tourism framework and practical guidance for developing resilient and restorative destinations